Internet sourcing and UK end consumer trend interest in the controlled medicines (opioids, sedatives and GABA drugs) in pre and post COVID-19 timeframes. (2021) - Whitfield, Mark; Germain, Jennifer; Hillis, Alice; Halsall, Devina; McVeigh, James; Abbasi, Yasir; Van Hout, Marie Claire
Abstract: Sourcing and self-medication of medicinal pharmaceuticals including those containing opioids obtained from non-regulated online suppliers is a serious public health issue. The main concerns include a lack of quality control, drug side effects, drug interactions, diversion and possible pathway to drug dependence. The internet offers increased availability and accessibility of these medicines through both legal routes obtaining pharmaceuticals on prescription and illegal routes via websites on both the surface and Dark Web. The impact of the current severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2 or COVID-19) pandemic reduced face-to face access for non-COVID-19 related health conditions and to drug treatment services. This study provides an overview of the extent of online sourcing of UK controlled medicines (opioids, sedatives and GABA drugs) from unregulated suppliers and estimates of customer interest, in particular focusing on the COVID-19 lockdown period in the UK, where access to some healthcare services was limited. Whilst it was not possible to identify an increase for online searches for controlled medicines over the past five years, or during the COVID-19 period, searches remained plentiful, in particular for oxycodone, morphine and diazepam. This study highlights the need for enhanced pharmacovigilance of non-regulated online suppliers and the imperatives of continued health messaging around the potential abuse of these controlled drugs and the dangers of using sites purporting to be regulated pharmacies.